The Role Of Nurses And Their Impact On Intensive Care Unit Outcomes (The Review of Diabetic Studies, 2024)
BackgroundCritical care nurses are essential in intensive care units (ICUs), delivering continuous monitoring, timely interventions, and multidisciplinary coordination for patients with life-threatening conditions. Their roles influence key outcomes like mortality, length of stay, and infection rates, with optimal staffing linked to 14% reduced hospital mortality and 20% fewer hospital-acquired infections. This review synthesizes evidence on nursing factors such as staffing ratios, education, and work environments amid rising patient acuity and shortages.​MethodsA systematic evaluation of observational studies from PubMed and related databases assessed critical care nursing impacts on ICU outcomes, without language or date limits, excluding non-peer-reviewed or pediatric data. The Newcastle-Ottawa Scale evaluated bias, and GRADE assessed evidence quality, focusing on quantitative associations like mortality odds ratios.​ResultsHigher nurse staffing and specialty certification correlated with lower ICU mortality (odds ratio 0.52), shorter stays by 1.5 days, and reduced adverse events like infections and delirium. Better work environments and protocol adherence improved failure-to-rescue rates and medication safety, though burnout affected 50% of staff, elevating risks.​ConclusionsCritical care nurses drive superior ICU outcomes through expertise and optimal conditions; policies must prioritize staffing standards (e.g., 1:1-1:2 ratios), training, and burnout mitigation to enhance safety and efficiency.​